Bats:: Neglected Agents of Sustainability - Uieda, Wilson; Bredt, Angelika (Sustainability in Debate, 2016)
When discussing sustainability, bats cannot be left out. These mammals have inhabited our Planet for more than 52 million years11 and, during this period, they have evolved into an incredible amount of species exploring a great variety of food and shelters. There is currently a worldwide distribution of 1,200 identified bat species. Among mammals, bats are only outnumbered by rodents, which account for a total of 2,500 species.